Синтез ванадійвмісних Ti-MCM-41 силікатів та їх каталітичні властивості в процесах дегідрування пропану - Redkina, A. V.; Konovalova, N. D.; Khomenko, K. N. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2014)
Ti-MCM-41 silicate with vanadium introduced in mesoporous structure has been obtained by hydrothermal template synthesis with participation of VOSO4 and pyrogenic titanoaerosil with 1.4 wt. % tetrahedrally coordinated titanium. By the X-ray diffraction, X-ray fluorescent spectroscopy, DR UV-vis analysis and adsorption of nitrogen it has been shown that even 0.3 wt. % V causes raising spatial order and hydrolytic stability of Ti-MCM-41. It has been found that additional supporting of VOx groups on a surface of the synthesized bimetallic silicate allowed to obtain the catalyst 5%VOx/V, Ti-MCM-41 which due to dehydrogenation of propane generated propylene with bigger selectivity and yield than those when VOx was supported on MCM-41 and Ti-MCM-41.